Acute Cerebrovascular Events With COVID-19 Infection. Issue 1 (January 2021) - Dhamoon, Mandip S.; Thaler, Alison; Gururangan, Kapil; Kohli, Amit; Sisniega, Daniella; Wheelwright, Danielle; Mensching, Connor; Fifi, Johanna T.; Fara, Michael G.; Jette, Nathalie; Cohen, Ella; Dave, Priya; et al.
Abstract : Background and Purpose: Coronavirus disease 2019 (COVID-19) has been associated with an increased incidence of thrombotic events, including stroke. However, characteristics and outcomes of COVID-19 patients with stroke are not well known. Methods: We conducted a retrospective observational study of risk factors, stroke characteristics, and short-term outcomes in a large health system in New York City. We included consecutively admitted patients with acute cerebrovascular events from March 1, 2020 through April 30, 2020. Data were stratified by COVID-19 status, and demographic variables, medical comorbidities, stroke characteristics, imaging results, and in-hospital outcomes were examined. Among COVID-19-positive patients, we also summarized laboratory test results. Results: Of 277 patients with stroke, 105 (38.0%) were COVID-19-positive. Compared with COVID-19-negative patients, COVID-19-positive patients were more likely to have a cryptogenic (51.8% versus 22.3%, P <0.0001) stroke cause and were more likely to suffer ischemic stroke in the temporal ( P =0.02), parietal ( P =0.002), occipital ( P =0.002), and cerebellar ( P =0.028) regions. In COVID-19-positive patients, mean coagulation markers were slightly elevated (prothrombin time 15.4±3.6 seconds, partial thromboplastin time 38.6±24.5 seconds, and international normalized ratio 1.4±1.3). Outcomes were worse among COVID-19-positive patients, including longer length of stay ( P <0.0001), greater percentage requiring intensive care unit care ( P =0.017), and greater rate of neurological worsening during admission ( P <0.0001); additionally, more COVID-19-positive patients suffered in-hospital death (33% versus 12.9%, P <0.0001). Conclusions: Baseline characteristics in patients with stroke were similar comparing those with and without COVID-19. However, COVID-19-positive patients were more likely to experience stroke in a lobar location, more commonly had a cryptogenic cause, and had worse outcomes.